STRATEGI MOTIVASI KARYAWAN KARYAWAN PT.NUSANTARA REGAS - Imron Rosadi; Nasruddin Nasruddin (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to determine the extent of the influence of the Work Environment and WorkDiscipline on Work Motivation and its implications for PT Nusantara Regas.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, namely as many as 65 people. The data processing method uses the pathanalysis method with the help of SPSS version 22.0. Statistical testing used individual parametersignificance test (t test) and simultaneous significance test (F test).The results showed that simultaneously the variables of Work Environment and WorkDiscipline on Work Motivation had a significant effect on employee performance. Partially itshows that analysis 1: work environment variables have a significant effect on employeeperformance, and analysis 2: work discipline variables have a significant effect on employeeperformance. Furthermore, in analysis 3: work motivation variables have a significant effect onemployee performance.Keywords: Work Environment, Work Discipline, Work Motivation and Employee Performance